The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/ijc.22682
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk and erythrocyte compositions of n‐3 highly unsaturated fatty acids in Japanese

Abstract: Dietary intake of fish rich in n-3 highly unsaturated fatty acids (HUFAs), such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), has been proposed to decrease cancer risk. In contrast to results from laboratory studies, however, protective effects for breast cancer have proved equivocal in epidemiological studies. In the present case-control study, we examined associations between breast cancer risk and fatty acid compositions in erythrocyte membranes as biomarkers for those intakes. Dietary info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
2
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 48 publications
11
59
2
6
Order By: Relevance
“…Our results are consistent with studies that find lower longchain omega-3 fatty acids and omega-3:6 ratios in RBCs (20,21) and adipose tissue (40,41) from women with breast cancer compared with controls. Omega-3 fatty acids are especially prone to oxidation (42), and it is possible that the lack of correlation between omega-3 fatty acids in blood and tissue and breast cancer risk in nested, case-control studies (22)(23)(24)(25)(26)(27)(28) is due to the complications of analyzing the fatty acid composition in samples stored for periods ranging from 4 to 25 years (23,25).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with studies that find lower longchain omega-3 fatty acids and omega-3:6 ratios in RBCs (20,21) and adipose tissue (40,41) from women with breast cancer compared with controls. Omega-3 fatty acids are especially prone to oxidation (42), and it is possible that the lack of correlation between omega-3 fatty acids in blood and tissue and breast cancer risk in nested, case-control studies (22)(23)(24)(25)(26)(27)(28) is due to the complications of analyzing the fatty acid composition in samples stored for periods ranging from 4 to 25 years (23,25).…”
Section: Discussionsupporting
confidence: 93%
“…Case-control studies generally find an inverse association between dietary intake and/or red blood cell (RBC) fatty acid content of EPA and DHA and breast cancer risk (19)(20)(21). Prospective studies also have generally shown an inverse association between consumption of omega-3 fatty acids from fish and/or fish oil supplements and breast cancer incidence (18).…”
Section: Introductionmentioning
confidence: 99%
“…Most prominently, this association has been noted in cultures such as Greenland, Alaska and Japan, where a natural high dietary intake of fish oils is maintained. As a result, a number of publications have been able to demonstrate that an increased consumption of omega-3 fatty acids such as EPA and DHA lead to a reduction in colorectal [ 143 , 144 , 145 ] and breast [ 146 ] cancer risk respectively. Clearly, the main role of omega-3 in tumourigenesis lies in the reduction of cancer risk and inhibition of cancer cell growth [147].…”
Section: Influence Of Dietary Fats On Aa Cascadementioning
confidence: 99%
“…29). The study design has been elsewhere described (29), and the investigation was executed in series within the Aichi Fatty Acid (AiFat) Research project to clarify associations between a large number of blood parameters and cancers in several sites (28,30,31). Briefly, all first-visit outpatients (n = 18,103), including all cancer cases (n = 3,972), were asked to fill out a questionnaire regarding their lifestyle and to provide 7-mL blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…Our questionnaire covered the following personal information: height, weight, dietary habits, habitual exercise, drinking habit, smoking status, and thorough medical information such as family history of cancer and current and prevalent history of diseases. Dietary assessment was elsewhere described in detail (30,31). In brief, average daily intakes of various foods and nutrients were assessed using a semiquantitative food frequency questionnaire with 47 food items, which had an acceptable relative validity and reproducibility for their consumption (33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%